2020
DOI: 10.1108/ejtd-04-2020-0066
|View full text |Cite
|
Sign up to set email alerts
|

Conditional factors for training activities in Chinese, Indian and Mexican subsidiaries of German companies

Abstract: Purpose The purpose of this paper is to analyse the qualification measures of 12 German multi-national companies (MNCs), all of which are present in China, India and Mexico. In particular, the transfer of dual initial training practices and further training measures are investigated. It examines the impact consistent training strategies across national borders have emerged in German companies or local arrangements have developed despite identical internal influencing factors. Design/methodology/approach Beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Although most comparative VET research has analysed transfer activities at the systemic level, some studies have focused on individual company levels, including those of Aring (2014), Li (2014), Gessler (2017), Wiemann and Pilz (2020), Vogelsang and Pilz (2020), Körbel, Pierenkemper, and Zibrowius (2017), Wiemann (2017), Peters (2018), andHolle (2019). The authors of these scholars have explored the extent to which German multinational companies practice dual vocational training in their subsidiaries abroad, and how this can inform the transferability of German vocational training abroad.…”
Section: Transfer In Comparative Vet Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most comparative VET research has analysed transfer activities at the systemic level, some studies have focused on individual company levels, including those of Aring (2014), Li (2014), Gessler (2017), Wiemann and Pilz (2020), Vogelsang and Pilz (2020), Körbel, Pierenkemper, and Zibrowius (2017), Wiemann (2017), Peters (2018), andHolle (2019). The authors of these scholars have explored the extent to which German multinational companies practice dual vocational training in their subsidiaries abroad, and how this can inform the transferability of German vocational training abroad.…”
Section: Transfer In Comparative Vet Researchmentioning
confidence: 99%
“…The findings have also revealed the strong influences of local conditions in this regard. For example, Wiemann and Pilz (2020) explored qualification strategies used by German multinational companies in India, Mexico, and China using both comparative VET research and applying the international human resource management perspective (see also Pilz and Wiemann 2020;Vogelsang and Pilz 2020;Fuchs 2020). They found that even in German companies in foreign countries, the dual training commonly used in Germany is only offered for a few specialists in some larger companies.…”
Section: Transfer In Comparative Vet Researchmentioning
confidence: 99%
“…Institutional quality management based on comprehensive models to initiate and steer educational and organisational development processes, as well as a general "culture of quality", are not well-established in the context of VET in India (Tara et al, 2016). The transfer of educational systems and practices is subject to context-dependent difficulties and obstacles that cause demand for contextualisation (Broadfoot, 2000;Vogelsang & Pilz, 2020). Crossnational policy borrowing frequently involves processes of adaptation (Phillips & Ochs, 2003), and often policies cannot be transferred entirely (Li, 2017;Pilz, 2017).…”
Section: Development Process Of Model Designmentioning
confidence: 99%
“…A comparison between India, Mexico and China illustrates that particularly smaller multinational companies need cooperation partners on a local level to provide training but that these partners must meet different local conditions (Fuchs, 2020; Pilz & Wiemann, 2020). Local conditions can vary, which has an influence on training concepts and thus also on cooperation between actors (Vogelsang & Pilz, 2020). For example, in India, many companies develop their own training concepts, whereas in China companies cooperate more with vocational schools and the German Chamber of Commerce (Pilz, 2016b; Pilz & Li, 2014; Vogelsang & Pilz, 2020).…”
Section: Conceptual Approach: Regional Actor Networkmentioning
confidence: 99%
“…Local conditions can vary, which has an influence on training concepts and thus also on cooperation between actors (Vogelsang & Pilz, 2020). For example, in India, many companies develop their own training concepts, whereas in China companies cooperate more with vocational schools and the German Chamber of Commerce (Pilz, 2016b; Pilz & Li, 2014; Vogelsang & Pilz, 2020).…”
Section: Conceptual Approach: Regional Actor Networkmentioning
confidence: 99%